Eksplorasi Dualistik Pendekatan dalam Pendidikan Islam: Perspektif Normatif Teks dan Dinamika Sosial Konstekstual: Penelitian - Syofrianisda; Suriyati; Tamrin Kamal; Sri Wahyuni; Rosniati Hakim (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study examines in depth the dynamics of two main approaches in Islamic education: the normative-textual approach and the socio-contextual approach. The normative-textual approach focuses on a literal understanding of Islamic texts, such as the Qur'an and Hadith, as sources of teaching that are fixed and absolute. Meanwhile, the contextual approach emphasises the importance of understanding religious messages in relation to the social, cultural, and historical contexts that surround them. This research aims to explore the tensions and possibilities of integrating the two approaches in developing a framework for Islamic education that is responsive to contemporary challenges without losing its normative essence. The findings indicate that an integrative approach that combines the strengths of both approaches can produce a more dynamic and adaptive understanding of Islamic education that remains rooted in the fundamental values of Islam. This study recommends the importance of methodological renewal in formulating Islamic curricula and learning strategies to avoid being trapped in the conservative versus progressive dichotomy.